Relationship of ACE1 and ACE2 genetic polymorphisms on SARS-CoV-2 infection and severity of symptoms in different regions of Iraq - Bilal Ali Khashan; Karkaz Mohammed Thalij; Ali Ameen Yaseen (Tikrit Journal of Pure Science)
This study was conducted in the laboratories of the Biology Department - College of Science - Tikrit University, the laboratories of the Food Science Department - College of Agriculture - University of Anbar, and the Public Health Laboratories - Anbar for the period from December 2021 AD until February 2022 AD,  study involved taking samples from hospitalized COVID-19 patients of both sexes, after a confirmed positive PCR test result. As well as those lying in quarantine in three Iraqi governorates (the isolation unit in Karkh, Yarmouk and Kadhimiya hospitals, the Al-Shifa quarry hospital in Anbar, the public health laboratory in Anbar, and the quarantine hospital for thousands in Erbil), in addition to outpatient clinics. They were distributed by 30 patients and 20 healthy subjects from each governorate, with ages ranging from 18-80 years, randomly to men and women in order to determine the role of genetic polymorphisms in the ACE inhibitor gene in the study samples. The results of the genetic polymorphisms of ACE-1rs4646994, ACE-2rs2106809, and ACE-2rs4240157 showed that there were non-significant differences between the frequency of alleles and genotypes in the patient's group compared with the healthy group. The DD mutant genotype of ACE-1rs4646994 appeared in the patient's group in Baghdad and Anbar with a high percentage, while patients in Erbil showed the highest percentage of the heterozygous genotype ID compared to healthy subjects, with an OR= 0.922, OR= 2.750, and OR= 1.118, respectively, for the mutant allele D. Therefore, it is not considered a risk factor for the disease in Baghdad, in contrast to Anbar and Erbil. The polymorphism of ACE-2rs2106809, the homozygous genotype CC was dominant in patients in the aforementioned provinces and may not be considered a risk factor for the disease. The results of ACE-2rs4240157 gene polymorphism, the heterozygous CT genotype showed a high percentage in patients in Baghdad and, while in Anbar patients, the normal genotype TT appeared to be the highest percentage compared to healthy subjects. The C mutant allele in Baghdad, Anbar, and Erbil patients reached OR= 1.306, OR= 4.333, and OR= 9.00, respectively, so this allele is considered a risk factor for the disease. We can conclude from this study the role of each of the polymorphisms rs4646994 ACE-1 and rs4240157 ACE-2 in infection with COVID-19 and the severity of its symptoms according to the geographical region and race, in contrast to rs2106809 ACE-2, as it is possible to conduct clinical studies to demonstrate the role of genetic polymorphisms with Relationship to diseases depending on the region and race.